DIVERSION AND RESTORATIVE JUSTICE IMPLEMENTATION IN INDONESIA'S JUVENILE COURT SYSTEM - Ika Darmika (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2019)
This study aims to find out and analyze: Regulation and implementation of diversion and restorative justice according to Law Number 11 of 2012 regarding Juvenile Court System, as well the obstacles encountered in implementing diversion and restorative justice in the Regency and City of Bogor. The method used in this study is normative juridical legal research method that is a legal research method which prioritizes secondary data (study of library materials) consisting of: primary, secondary, and tertiary law materials. The study result reveals that diversion and restorative justice as regulated inLaw Number 11 of 2012 regarding Juvenile Court System has been in accordance juridically with International Instrument, such as The Beijing Rules, new theories in the field of Juvenile Laws and Juvenile Court System, also International Instrument (ECOSOC Resolution 1987/57).